From Monuments to Movements: Curating an Artistic Re-imagination of Kedah Tua - Nur Hilyati Ramli; Mumtaz Begum Aboo Backer; Pravina Manoharan (Wacana Seni Journal of Arts Discourse, 2019)
This article presents a performative reflection of the archaeological discoveries from Kedah Tua's early civilisation envisioned through the site-specific theatrical project entitled "Bermulanya Di Sini…Kedah Tua". Different elements from archaeological excavations were selected and adapted into a performance project by way of the curation of theatrical movements. The interpretation of the archaeological findings is translated using specific elements from the study of performing arts such as movement, space, and time to help simplify the dissemination of an otherwise complex knowledge of historical data. The movements choreographed for the different dance scenes and overall performance are based on the archaeological findings of metal, monuments, and an industrialised civilisation. Recent interest in performing arts as a reflection of the archaeological discoveries can be seen as an attempt to broaden the scope of archaeology as a discipline to encompass the totality of the human experience. This collaborative work between the field of archaeology and performance presents choreographers with interesting approaches in exploring notions concerning the performing arts.